Psychological changes toward the value of learning judo and impressions of judo lessons in junior high school students experiencing judo for the first time - Kiruma, M.; Ishikawa, Y.; Matsui, T.; Kubota, H.; Yogi, Y. (American Journal of Sports Science, 2023)
This study was conducted in Japan, where Judo has become a part of compulsory education in junior high school. The studied the experiences of 254 junior high students learning Judo for the first time were examined with respect to the value of learning traditional behavior, including respectful attitudes and manners toward the fighting opponent; their impression of the sport, such as whether it is fun or scary; and how these change through the learning process. The classes were planned to include five sessions. The main learning contents were structured with an emphasis on teaching "knowledge," "skills," and "attitudes."". The students were asked to participate in a pre-class and post-class survey consisting of 26 items created by the authors to examine their psychological change. The results demonstrated that there were significant changes in the students` responses to items such as "It is necessary to conduct Judo classes in Physical Education given how the sport is a unique culture of Japan" and "My impression of Physical Education classes is that they are `fun`." In addition, their fear of Judo, such as having an impression that Judo lessons were "painful" and "scary," also reduced. This study identified psychological changes in junior high school students` perspectives toward the value of learning Judo and their impression of Judo lessons for those experiencing Judo for the first time. Its findings will contribute to enriching Judo instruction in junior high school and at Judo clubs with students around the same age.